PENDAMPINGAN UMKM BERBASIS LEGALITAS USAHA, PENCATATAN KEUANGAN, DAN PEMASARAN DIGITAL DI KOTA KUPANG - Soleman Nub Uf; Marsi Bani (CV. Kalimasada Group, 2026)
Micro, Small, and Medium Enterprises (MSMEs) play a strategic role in strengthening local economies, creating employment opportunities, and improving household income. Kupang City, as the capital of East Nusa Tenggara Province, has significant MSME potential, particularly in culinary businesses, small trade, creative products, and household services. However, many MSME actors still face challenges related to business legality, simple financial recording, product packaging, and digital marketing. This community service program aimed to improve the capacity of MSME actors in Kupang City through assistance in business legality, simple bookkeeping, product packaging improvement, and digital marketing utilization. The program was conducted from January to February and involved 25 MSME actors from culinary, handicraft, small trading, and service sectors. The method used was a participatory approach consisting of initial observation, training, direct practice, field mentoring, evaluation, and monitoring. The results showed an increase in participants’ understanding, as indicated by the average pretest score of 58.4, which increased to 84.2 in the posttest. In addition, 80% of participants were able to prepare simple financial records, 72% improved their product packaging or business identity, 76% actively used social media for promotion, and 60% experienced an increase in sales turnover during the mentoring period. These findings indicate that practical and continuous mentoring has a positive impact on improving MSME literacy, business management skills, market reach, and business independence. Continuous assistance is needed to support MSMEs in Kupang City to become more legal, adaptive, competitive, and sustainable in the digital economy era.